1987
DOI: 10.1007/bf01533762
|View full text |Cite
|
Sign up to set email alerts
|

Emotional factors and the in vitro fertilization and embryo transfer process

Abstract: In vitro fertilization is nearly always a treatment of a last resort. This fact, along with the treatment's multiplicity of procedures and intensity, place unique emotional demands on patients. The goal of this research was to describe both the acknowledged emotional state of patients at the time they began the in vitro fertilization and embryo transfer (IVF-ET) process and the emotional experience of the actual procedures themselves. The findings can be used to develop strategies for providing emotional suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(37 citation statements)
references
References 10 publications
1
32
0
4
Order By: Relevance
“…The psychological burden associated with fertility treatment appears to have an important impact on women's decision to stop treatment [1,6,9] . Many patients experience considerable psychological burden not only while participating in fertility treatment [10] , but also following diagnosis and during the clinical investigation of infertility [11,12] .…”
Section: Discussionmentioning
confidence: 99%
“…The psychological burden associated with fertility treatment appears to have an important impact on women's decision to stop treatment [1,6,9] . Many patients experience considerable psychological burden not only while participating in fertility treatment [10] , but also following diagnosis and during the clinical investigation of infertility [11,12] .…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-three percent of the women and 38% of the men expected that IVF treatment would be extremely stressful. Mahlstedt et al (2) analyzed responses from 94 IVF patients. They found that 82% of the patients did not view the decision to enter the IVF program to be a difficult one and that upon entry to the program 56% of patients indicated they would repeat the IVF treatment if the initial procedure was not successful.…”
Section: ~Troductionmentioning
confidence: 99%
“…Grief and depressive symptoms have been described as typical reactions to a failed cycle (10). Though most recover quickly from these symPtoms and go on to another cycle, a minority suffer more severe grief reactions (9), and one study described patients who discontinued treatment as a result of the emotional strain following a failed cycle (5).…”
Section: What Is So Stressful About This Technology?mentioning
confidence: 99%
“…4,1997 resulted in the first successful birth in 1978, a myriad of studies on the psychological profile of participants in these programs has appeared in the literature (1-3). Evidence of serious psychopathology in this patient population is rare, but the ART experience appears to have a profound psychological affect on participants (4,5). Accordingly, the need for counseling and support in this treatment milieu has been clearly demonstrated.…”
mentioning
confidence: 98%